Unemployment in terms of socio-economic - Pawlak, Adam (Journal of Education, Health and Sport, 2019)
Unemployment is a condition in which people of working age may take up employment and wishing to remain without work. In Poland, this phenomenon is associated with marketisation of the economy, and you can point out that virtually every country in which the force is a market economy there more or less unemployment. Theorists suggest that a low level of unemployment is positive for the economy because it contributes to the phenomenon postania competition which brings benefits for both employers and potential employees. However, in the case of Polish, which is trading at a relatively high level of unemployment is a problem for both economic and social. Unemployment brings consequences for the economy. In addition to lower income or lower tax revenues, unemployment in many cases entails the need to incur expenditure on social welfare and health care. Unemployment also causes negative consequences for individuals. These are extremely broad issues, which remain valid and for this reason are widely discussed in the available literature.